Prenatal diagnosis, natural history, postnatal treatment and outcome of 222 cases of spina bifida: experience of a tertiary center. (11th February 2019) - Masini, L.; De Luca, C.; Noia, G.; Caruso, A.; Lanzone, A.; Rendeli, C.; Ausili, E.; Massimi, L.; Tamburrini, G.; Apicella, M.; De Santis, M.
ABSTRACT: Objectives: To report on the prenatal ultrasonographic diagnosis of spina bifida (SB) and its natural history, treatment and long‐term outcome in a large tertiary referral center. Methods: All cases of SB diagnosed between February 1980 and December 2015 in the Obstetric Prenatal Diagnosis Day Unit of the Obstetrics and Gynecology Department at the Catholic University of the Sacred Heart, Rome, were reviewed. All infants with an open defect were delivered by elective Cesarean section and underwent early repair of the spinal defect. A ventriculoperitoneal (VP) shunt and/or third ventriculostomy was performed when needed. Complete postnatal follow‐up was carried out by our multidisciplinary team in the majority of cases. The cohort was analyzed in two groups: Group 1 included patients referred between February 1980 and December 1999; Group 2 included patients referred between January 2000 and December 2015. Results: There was a total of 222 cases of SB with a prenatal diagnosis rate of 94.6% ( n = 210), with the majority of defects being meningomyeloceles ( n = 142 (64.0%)), affecting the lumbosacral level ( n = 110 (49.5%)) and being ≥ 2 cm in size ( n = 163/195 (83.6%)). There were 174 (78.4%) live births, with more terminations in Group 2 (26.1%) than in Group 1 (10.8%; P = 0.003). Postnatal surgical repair was conducted in 157 cases (99.4% of eligible cases), with death of an infant who was operated on occurring more often in Group 1 (14.1%) than in Group 2 (4.2%; P = 0.03). VP shunt placement was required in 60.3% of infants operated on after January 2000. Long‐term follow‐up was available for 136 children (111 with open defects and 25 with closed defects). Infants born since 2000 with an open defect had normal ambulation or a mild defect in 50% of cases and normal or mild deficit of sphincter function in 37.8% of cases. An intelligence quotient of ≥ 70 was observed in the majority of children (81.4%; 35/43 cases). Worse motor function was associated with progressive prenatal ventriculomegaly, level of lesion and VP shunt placement. Conclusions: We describe the prenatal diagnosis, natural history and long‐term outcome of a large contemporary cohort of SB fetuses and infants. In an era of pioneering fetal surgical techniques for in‐utero SB repair, it is important to acknowledge that advances in conventional neonatology and pediatric neurosurgery have allowed increased life expectancy and improved quality of life in patients with SB. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2018; 53: 287–289